Open-ended coaxial waveguide for conical-beam radiation - Shen, Zhongxiang (2013)
This communication demonstrates that an open-ended coaxial waveguide can be a good aperture antenna for generating conical-beam radiation. Design equations are derived to obtain the radii of inner and outer conductors of a coaxial waveguide radiating into a half free space. A design example is provided to verify the design concept and derived equations. Simulated and measured results of a fabricated aperture antenna are presented and compared to demonstrate its conical-beam radiation performance.